Screening of Candidate Gene of Diabetes Mellitus Type 1 in Dogs by Bioinformatics Translational Study - Shodiq Permata, Fajar (Translational Research in Veterinary Science, 2024)
National Center for Biotechnology Information (NCBI) is an extensively impacted genetic database for big data analysis for bioinformatics studies in all organisms. At the same time, Human-Mouse: Disease Connection (HMDC) is a complete database for mutated gene information in many human and mouse disease models. Diabetes mellitus (DM) type 1 is a common and deadly degenerative disease in dogs, so looking for candidate genes for type 1 DM)genetic markers in dogs is essential. This study aimed to search for candidate genetic markers of DM type 1 in dogs by comparing human and mouse model databases through bioinformatics studies. This study used the HMDC database to find candidate genes of type 1 DM genetic markers with endocrine system disease limitations, then continued to check the accession number and similarity of nucleotide identity from each genetic marker, comparing dogs, humans, and mice. The results identified as many as seven candidate genes for DM type 1 genetic markers in dogs out of 16 candidate genes for DM type 1 humans and mice models. This study concluded that utilizing NCBI and HMDC tools could find the candidate genes for DM type 1 genetic markers in dogs. The findings contribute to molecular diagnostic demand in veterinary medicine, especially for dogs’ DM disease